Increased risk of erectile dysfunction among patients with sleep disorders: a nationwide population‐based cohort study. Issue 8 (24th February 2015) - Lin, H.‐H.; Ho, F.‐M.; Chen, Y.‐F.; Tseng, C.‐M.; Ho, C.‐C.; Chung, W.‐S.
Summary Aims Few studies have investigated the relationship between sleep disorders (SD) and erectile dysfunction (ED). Therefore, this study explored whether patients with SD in an Asian population are at an increased risk of developing ED. Methods This longitudinal nationwide population‐based cohort study investigated the incidence and risk of developing ED in 34, 548 men newly diagnosed with SD between 2002 and 2008 from the National Health Insurance Research Database. A total of 138, 192 controls without SD were randomly recruited from the general population and frequency matched according to age and sex. The follow‐up period began from the date of entering the study cohort until the date of an ED event, censoring, or 31 December 2010. We conducted Cox proportional hazard regression analyses to estimate the effects of SD on the risk of ED. Results The SD cohort had a 2.11‐fold adjusted hazard ratio (HR) of subsequent ED development compared with the non‐SD cohort [95% confidence interval (CI) = 1.89–2.37]. The incidence of ED increased with age for both cohorts and was higher for the patients in the SD cohort. Compared with the participants without SD or comorbidities, the patients without SD with any comorbidity exhibited a 1.79‐fold risk of developing ED (95% CI = 1.54–2.09); the highest risk was for those with both SD and any comorbidity (HR = 3.34, 95% CI = 2.82–3.95). Furthermore, SD patients who had a particular number of comorbidities showed the dose–response effect of developing ED. Conclusion This nationwide cohort study determined that ED risk evidently increased in SD patients compared with the general population.